Pengaruh Ekstrak Buah Bakau (Rhizophora sp) terhadap Ekspresi Monocyte Chemoattractant Protein-1 pada Aorta Tikus Aterosklerosis - Muhammad Yulis Hamidy; Huriatul Masdar; Ayu Trisya Arti (Jurnal Ilmu Kedokteran, 2023)
Atherosclerosis is an atheromatous plaque that protrudes into and clogs blood vessels. This study aimed to analyze the effect of Rhizophora sp extract on the expression of Monocyte Chemoattractant Protein-1 (MCP-1) in the early stages of atherosclerosis in rats fed an atherogenic diet. Eighteen abdominal aortic paraffin blocks of white rats were used, consisting of 3 groups: normal diet (K1), atherogenic diet (K2), and atherogenic diet and Rhizophora sp extract (K3). The effect of Rhizophora sp extract was assessed by immunohistochemical examination. MCP-1 expression was calculated in 5 fields of view, then analyzed using Photoshop Image Analysis. The results of this study indicated that administration of Rhizophora sp extract reduced MCP-1 expression in K3 compared to K2 (0.155±0.075 vs 0.246±0.097) although this result was not statistically significant. In conclusion, Rhizophora sp extract has the ability to inhibit MCP-1 expression in the aorta of rats fed an atherogenic diet.